Respon Seedling Durian Merah Lokal (Durio graveolens) terhadap Konsentrasi Penggunaan Bakteri Fotosintesis - ., Wahyudi; ., Mawardi (JURNAL AGROPLANT, 2024)
This research aims to determine the response of local red durian seedlings to the use of photosynthetic bacteria, as well as to determine the appropriate concentration dose of photosynthetic bacteria for local red durian seedlings. This research was carried out in Pancakarya Village, Ajung District, Jember Regency, East Java, at an altitude of 50 meters above sea level. This research was carried out from December 2022 to February 2023. This research used a Randomized Completed Block Design (RCBD), with 6 treatment doses of PSB fertilizer, consisting of K0 (control); K1 (5 ml); K2 (10 ml); K3 (15 ml); K4 (20 ml); K5 (25 ml), with 5 repetitions. The parameters observed in this research included plant height, stem diameter, number of leaves, leaf length and leaf width, number of branches, and number of roots. The results of the analysis of variance of all observed parameters, which include plant height, stem diameter, number of leaves, leaf width, number of branches, root length and leaf length, show that giving PSB to local durian seedlings did not have a significant effect on all observed variables. , except for the plant height variable.